PENERAPAN APLIKASI CANVA DALAM PEMBUATAN MEDIA PROMOSI KESEHATAN DI POSYANDU MAWAR CITEUREUP-BOGOR - Sri Redjeki; Nurhayati Pratiwi; Ahmad Yani Prasetya (Khidmatussifa: Journal of Islamic Studies, 2025)
In the increasingly digital era, the use of digital media has become an efficient tool for providing health information to the public. Canva is a design application that offers various services such as presentations, resumes, posters, pamphlets, brochures, graphics, infographics, banners, bookmarks, bulletins, and more. Integrated health service post (Posyandu) officers and young people use Canva to help create engaging and easy-to-understand health promotion materials for dissemination to the community in the Mawar Citeurep Posyandu area. By using Canva to create visually appealing designs, it is hoped that this will improve public health.